Characterizing Ultra-Processed Foods by Energy Density, Nutrient Density, and Cost - Gupta, Shilpi; Hawk, Terry; Aggarwal, Anju; Drewnowski, Adam (Frontiers in Nutrition, 2019)
Background: The NOVA food classification scheme divides foods into ultra-processed, processed, unprocessed, and culinary ingredients. Ultra-processed foods contribute >60% of energy to diets in the US. Objective: To characterize ultra-processed foods by energy density, nutrient density, and monetary cost. Methods: The 384 component foods of Fred Hutch (FHCRC) food frequency questionnaire (FFQ), were assigned to 4 NOVA categories and to 7 USDA MyPyramid food groups. Energy density was kcal/g . Nutrient density was measured using the Nutrient Rich Food index NRF9.3. Food prices were collected in local supermarkets from 2004 to2016. Analyses examined time trends in food prices by NOVA category and by USDA food group.. Results: The ultra-processed classification captured mostly grains (91%), fats and sweets (73%), dairy (71%), and beans, nuts and seeds (70%), but only 36% of meat, poultry and fish, 26% of vegetables, and 20% of fruit. Compared to unprocessed foods, ultra-processed foods had lower nutrient density (NRF9.3 per 100kcal: 21.2 vs. 108.5) ,higher energy density (mean (SD): 2.2 vs 1.10 in kcal/g), and lower per calorie cost (0.55 vs. 1.45 in $/100 kcal). Ultra-processed foods did not increase in price as much as unprocessed foods over the 12 year period.. Conclusion: Ultra-processed foods tend to be energy-dense, low-cost, and nutrient-poor. Low energy cost could be one mechanism linking ultra-processed foods with negative health outcomes. Food-based Dietary Guidelines may need to address food processing in relation to economic aspects of food choice.